Characteristics of volcanic gas correlated to the eruption activity; Case study in the Merapi Volcano, periods of 1990-1994 - Priatna, Priatna; Kadarsetia, Eka (Geological Agency, 2007)
http://dx.doi.org/10.17014/ijog.vol2no4.20074Volcanic gases, collected from Gendol and Woro solfatara fields, the summit of Merapi Volcano during 1990-1994, show an increase in chemical composition of H , CO, CO , SO , and HCl prior to the volcanic events, on the contrary to the drastic decreasing water vapour. The carbon/sulfur ratio of the volcanic gases lies between 1.5 and 5.7 which means that they were derived from the fresh magma. The Apparent Equilibrium Temperature (AET) which is calculated from chemical compositions of volcanic gases using reaction of SO +3H = H S+2H O showed an increasing value prior to the volcanic events. The Merapi activities lasted during August 1990 to November 1994 showed a significant increase in ratio SO /H S prior to the November 1994 pyroclastic flow. The isotopic composition of volcanic gas condensates indicates that water vapour in Gendol is directly derived from the fresh magma. On the other hand, the contamination and cooling by the subsurface water occurred around the Woro field at a shallow part.Â